Taxonomy Meets Neurology, the Case of Amyotrophic Lateral Sclerosis - Morello, Giovanna; Spampinato, Antonio Gianmaria; Conforti, Francesca Luisa; Cavallaro, Sebastiano (Frontiers in Neuroscience, 2018)
Recent landmark publications from our research group outline a transformative approach to defining, studying and treating amyotrophic lateral sclerosis (ALS). Rather than approaching ALS as a single entity, we advocate targeting therapies to distinct “clusters” of patients based on their specific genomic and molecular features. Our findings point to the existence of a molecular taxonomy for ALS, bringing us a step closer to the establishment of a precision medicine approach in neurology practice.